2008
DOI: 10.1590/s0102-09352008000200004
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for Staphylococcus aureus DNA isolation

Abstract: This study describes a rapid procedure for the isolation of genomic DNA from Staphylococcus aureus that yielded a good amount of high quality DNA for the amplification of staphylococcal enterotoxins genes (A, B, C, D, and E) and the TSST-1 gene as well as enzymatic restriction (HaeIII) from environmental isolates. With this method, it was possible to detect these genes in a sample containing as little as 10 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…Since S.aureus does not compete with indigenous microorganisms within raw milk and dairy products, staphylococcal contamination is usually associated with improper handling of food materials, followed by storage under poor environmental conditions (12). Staphylococcus aureus is also present in animals; dairy cattle (10), sheep, and goats, particularly if they are affected by subclinical mastitis, are likely the source of milk contamination (11).…”
Section: Introductionmentioning
confidence: 99%
“…Since S.aureus does not compete with indigenous microorganisms within raw milk and dairy products, staphylococcal contamination is usually associated with improper handling of food materials, followed by storage under poor environmental conditions (12). Staphylococcus aureus is also present in animals; dairy cattle (10), sheep, and goats, particularly if they are affected by subclinical mastitis, are likely the source of milk contamination (11).…”
Section: Introductionmentioning
confidence: 99%
“…They designed primers specific for the nuc gene (NUC1-NUC2 for S. aureus, NUC3-NUC4 for S. hyicus and NUC5-NUC6 for S. intermedius) and detected three target species by MPCR, directly from bovine whole milk, with adequate specificity and acceptable detection limit for identification of coagulase positive Staphylococcus (CPS) in foods with the detection limit of 10 3 CFU/ml which is in contrast to our study as we could not multiplex One plausible reason might be the cell wall of gram positive bacteria, that contains vide variety of molecules that serve to provide rigid exoskeleton for protection against both mechanical and osmotic lysis. It has been observed that Staphylococcus aureus detection from milk by molecular techniques was reported when lysostaphin a peptidase produced by Streptococcus simulans that break the cellular membrane of Staphylococcus aureus was used in DNA extraction protocol (Chapaval et al, 2008). We too attribute it due to the difference between extraction of DNA from Gram positive and Gram negative or it may be possible that template DNA of Staphylococcus required more sophisticated approach which we did not apply because we wanted to use multiplex directly on field samples.…”
Section: Evaluation Of Mpcr On Field Samplesmentioning
confidence: 98%
“…Various protocols have been described for the extraction of DNA from specific groups of microorganisms; however, the efficiency of these protocols varies among different groups (Baratto and Megiolaro, 2012;Chapaval et al, 2008;Ligozzi and Fontana, 2003;Rivera et al, 2003;Wilson, 1997). This variation is mainly due to the inherent characteristics of the different bacterial groups and the structure of their cell walls, which reflects the efficiency of lysis.…”
Section: Choice Of a Single Protocol For Gram Positive And Negative Bmentioning
confidence: 99%